Metode Penafsiran Al-Tafsir Al-Munir Karya Muhammad Nawawi Al-Jawi - M. Solahudin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2021)
Interpretation is an effort to comprehend the Qur'an comprehensively from all sides of the scientific field. Both in terms of methods, styles and other approaches that can contribute scientifically. Many Mufassirs have made positive contributions to interpretation, both from international and local (Indonesia) Mufassirs, among Mufassirs from Indonesia, namely Muhammad Nawawi al-Jawi, he was a great scholar of his time. His work Al-Tafsir al-Munir and dozens of other works are evidence of his greatness as a scholar. In this article, we will explain how Muhammad Nawawi's biography, his interpretation method and style.